How Organizations Move from Stigma to Legitimacy: The Case of Cook’s Travel Agency in Victorian Britain - Hampel, Christian E.; Tracey, Paul (Academy of Management Journal, 2017)
Based on an in-depth historical study of how Thomas Cook’s travel agency moved from stigmatization to legitimacy among the elite of Victorian Britain, we develop a model of organizational destigmatization. We find that audiences stigmatize an organization because they fear that it threatens a particular moral order, which leads them to mount sustained attacks designed to weaken or eradicate the organization. Our model suggests that an organization that experiences this form of profound disapproval can nonetheless purge its stigma and become legitimate through a two-step process: first the organization engages in stigma reduction work designed to minimize overt hostility among audiences by showing that it does not pose a risk to them. Second it engages in stigma elimination work designed to gain support from stigmatizers by showing that it plays a positive role in society. Our study therefore reorients organizational stigma research from a focus on how organizations can cope with the effects of stigma, and considers instead how they can eradicate the stigma altogether. We also shed light on much neglected audience-level dynamics by examining the process through which audiences construct stigma and why these constructions may change.